The Students’ Engagement in Foreign Language Learning through ICT Incorporation - Purnawati Purnawati; Zainal Rafli; Syamsi Setiadi (Journal of English Language Teaching and Linguistics, 2024)
In this 21st century, the incorporation of Information and Communication Technology (ICT) has become a prominent practice in various educational domains, including the learning of languages in the classroom. However, there are a small number of teachers who are not familiar with incorporating ICT in their classrooms due to numerous causes. By the given situation, this study aims to identify the disparities in students' engagement between English as a Foreign Language (EFL) classrooms that utilize Information and Communication Technology (ICT) and those that do not. Additionally, it seeks to determine the predominant and higher forms of engagement in these two types of EFL classrooms. A descriptive qualitative approach was applied in this research. To obtain the data, the authors examined the level of student involvement during teaching and learning activities in two types of classrooms: those that employed ICT (Information and Communication Technology) and those that did not. Subsequently, the acquired data was scrutinized and categorized based on the parameters of students' involvement (behavioral, cognitive, and emotional). The results indicate that both classrooms are primarily characterized by students' behavioral involvement. The class that included ICT in its teaching and learning process experienced a 9.5% increase in students' cognitive engagement. The implication of this research is to encourage teachers to incorporate ICT in the classroom so that the students’ three engagement types can be achieved better proportionally.